In vitro maturation of fully active [FeFe]-hydrogenase in a defined system including the iron carrier NfuA - Alexander Marlott; Adrien Pagnier; Eric M. Shepard; Batuhan Balci; Abraham Teye; Douglas M. Warui; Hao Yang; Alex Drena; Squire J. Booker; Brian M. Hoffman; William E. Broderick; Joan B. Broderick (Proceedings of the National Academy of Sciences, 2025)
The [FeFe]-hydrogenase employs an active-site 6Fe H-cluster to catalyze the reversible reduction of protons to H 2 . A [4Fe-4S] subcluster of the H-cluster is synthesized by housekeeping iron-sulfur cluster assembly machinery, and then dedicated hydrogenase maturation enzymes, together with components of the glycine cleavage system, build and deliver a [2Fe] subcluster to generate the full H-cluster. Here, we report that the Escherichia coli iron-sulfur carrier protein NfuA supports in vitro maturation of fully active [FeFe]-hydrogenase, with H 2 production rates comparable to that of the in vivo - matured Chlamydomonas reinhardtii [FeFe]-hydrogenase ( Cr HydA). Inclusion of NfuA in the in vitro maturation process improves its efficacy by delivering the iron essential for formation of the [Fe II (cys)(CN)(CO) 2 ] – synthon at the dangler iron site of the HydG auxiliary cluster. NfuA serves an additional role in reconstituting and maintaining the catalytically essential iron-sulfur clusters on the maturase enzymes HydE, HydF, and HydG. Further inclusion of a high CO affinity myoglobin variant (Mb H64L ) sequesters free CO generated during the maturation process, minimizing formation of the CO-inhibited H ox -CO enzyme state, significantly increasing hydrogenase activity. The addition of NfuA and Mb H64L to the fully defined maturation system thus results in an in vitro [FeFe]-hydrogenase maturation system that generates highly active enzyme while providing insights into factors important to in vivo maturation.